Early Venous Thrombosis - Day, T. K; Cowper, S. V; Kakkar, V. V; Clark, K. G. A (Thrombosis and Haemostasis, 1977)
The passage of a minimal electric charge was used to initiate thrombosis in rabbit femoral veins, and the events occurring during formation of the thrombus were observed using scanning electron microscopy. Thrombosis began to occur within ten minutes after passage of the charge, upon an apparently unaltered endothelium. The first event was the laying down of a fibrin meshwork and this was shortly followed by the appearance of regularly arranged platelet clumps.